Antimicrobial peptides for the prevention and treatment of dental caries: A concise review - Niu, John Yun; Yin, Iris Xiaoxue; Wu, William Ka Kei; Li, Quan-Li; Mei, May Lei; Chu, Chun Hung (Archives of oral biology, 2021)
•Antimicrobial peptides are naturally occurring protein molecules with antibacterial, antiviral and/or antifungal activity.•Antimicrobial peptides receive considerable attention in novel therapeutics, especially in dental caries.•Maintaining tooth minerals and controlling oral microbial biofilms are essential for preventing caries development.•This concise review describes previous results on the bactericidal property of natural antimicrobial peptides against Streptococcus mutans.•This concise review also indicated several synthetic antimicrobial peptides were bactericidal, particularly for Streptococcus mutans. Some synthetic antimicrobial peptides prevented bacterial adhesion, while few antimicrobial peptides showed remineralising properties for hydroxyapatite. The objective of this study was to perform a comprehensive review of the use of antimicrobial peptides for the prevention and treatment of dental caries. The study included publications in the English language that addressed the use of antimicrobial peptides in the prevention and treatment of caries. These publications were also searchable on PubMed, Web of Science, Embase, Scopus, the Collection of Anti-Microbial Peptides and the Antimicrobial Peptide Database. A total of 3,436 publications were identified, and 67 publications were included. Eight publications reported seven natural human antimicrobial peptides as bactericidal to Streptococcus mutans. Fifty-nine publications reported 43 synthetic antimicrobial peptides developed to mimic natural antimicrobial peptides, fusing peptides with functional sequences and implementing new designs. The 43 synthetic antimicrobial peptides were effective against Streptococcus mutans, and nine peptides specifically targeted Streptococcus mutans. Ten antimicrobial peptides had an affinity for hydroxyapatite to prevent bacterial adhesion. Six antimicrobial peptides were also antifungal. Four antimicrobial peptides promoted remineralisation or prevented the demineralisation of teeth by binding calcium to hydroxyapatite. In conclusion, this study identified 67 works in the literature that reported seven natural and 43 synthetic antimicrobial peptides for the prevention and treatment of caries. Most of the antimicrobial peptides were bactericidal, and some prevented bacterial adhesion. A few antimicrobial peptides displayed remineralising properties with hydroxyapatite.